Religion and progress in modern Asia - Bellah, Robert N. (Free Press ; Collier-Macmillan, 1965)
This volume is based on papers presented to a conference on Cultural Motivations to progress in south and southeast Asia held in Manila from the third to the eigth of June, 1963, and on excerpts and summaries of discussions that took place during the conference.